(NlINEJNAQ ALGEBRA I DIFFERENCIALXNAQ GEOMETRIQ (B:s (NlEKCII PO GEOMETRII(B. II (NSEMESTR (B: (Nu^EBNOE POSOBIE (B/s - (NpOSTNIKOW(B, (NmIHAIL mIHAJLOWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1979)
(NpREDM(B. (NUKAZ(B.: (NS(B. 310-312s
Keywords: (NdIFFERENCIALXNAQ GEOMETRIQs; (NlINEJNAQ ALGEBRAs